THE FUTURE OF FDI IN SOUTH EASTERN EUROPEAN COUNTRIES: MESSAGES FROM NEW EU MEMBER STATES - Penev, Slavica; Rojec, Matija (Economic Annals, 2014)
This paper looks at the interlinking of inward FDI, EU accession, and transition-related structural reform processes, and identifies the largest lags of SEE-6 countries in EU accession and transition processes, whose removal would have a positive impact on inward FDI. The analysis is based on EBRD Transition Indicators, the World Bank Doing Business Index, and the World Bank Governance Index. We find an obvious correlation of inward FDI, transition, and EU accession processes of NMS-10 countries and claim that SEE-6 countries will broadly follow the same pattern: their relative position as FDI recipients will gradually improve along with the progress of EU accession and transition processes. The analysis identifies the following main gaps of the SEE-6 in these processes: (i) in terms of economic system development - enterprise restructuring and governance, and sectoral reforms in energy, infrastructure, capital markets, and private equity; (ii) in terms of the governance of economy and society at large - regulatory quality and rule of law; and (iii) in terms of the business environment - dealing with construction permits, enforcing contracts, and registering property. Progress in narrowing down these gaps would mean a step forward in EU accession and transition, and consequently an improvement of SEE-6 countries’ positions as locations for inward FDI.